2020
DOI: 10.1177/0950422220980920
|View full text |Cite
|
Sign up to set email alerts
|

The importance of part-time work to UK university students

Abstract: The purpose of this paper is to examine the skills requirements of UK graduate jobs and to compare them to those for part-time jobs typically undertaken by UK university students in order to identify similarities and/or differences between them. A content analysis of 100 graduate jobs and 100 part-time jobs was used as the basis of comparison. The person skills criteria were initially noted for graduate jobs and were then compared to the skills required for the part-time jobs. Quantitative analysis was carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Murray et al, (2019) found similar views of civil engineering students employed in non-engineering summer jobs, with self-reported improvements in their communication and teamworking skills. Of note, Evans & Yusof (2020) have argued for students' who secure part time work to consider how this can help demonstrate the skills required in their future professional careers, and, for employers of students to consider how they can assist them in skills development rather than only monetary benefits.…”
Section: Extra-curricular Activitiesmentioning
confidence: 99%
“…Murray et al, (2019) found similar views of civil engineering students employed in non-engineering summer jobs, with self-reported improvements in their communication and teamworking skills. Of note, Evans & Yusof (2020) have argued for students' who secure part time work to consider how this can help demonstrate the skills required in their future professional careers, and, for employers of students to consider how they can assist them in skills development rather than only monetary benefits.…”
Section: Extra-curricular Activitiesmentioning
confidence: 99%
“…Despite the fact that in some cases attendance was directly impacted by a student's 2 requirement to work alongside their degree, the main benefit of some paid work for university students is the development of key skills which could prove useful for careers post-graduation (Evans & Yusof, 2021).…”
Section: Introductionmentioning
confidence: 99%